UJI CO-FIRING BAHAN BAKAR SEMI RENEWABLE CAMPURAN BATUBARA DAN LIMBAH SERBUK GERGAJI BATANG KELAPA - Sadul, Alvira; Aladin, Andi; Rasyid, Rismawati (Journal of Scientech Research and Development, 2024)
The present study delves into the current exploration and research surrounding alternative energy sources, particularly the utilization of agricultural waste biomass as a potential fuel. Specifically, the study investigates the viability of coconut stem sawdust, a prevalent agricultural byproduct, as a supplementary energy source. The calorific value of coconut stem sawdust is established at 4304 Kcal/kg. This biomass material is then subjected to blending with coal, characterized by a calorific value of 5761 Kcal/kg, for application in a steam power generation facility. Prior to its integration into the co-firing process, the coconut sawdust undergoes a preparatory phase where it is divided into two distinct samples: untreated sawdust and sawdust derived from pyrolyzed coconut stems. Pyrolysis, facilitated by nitrogen gas at a flow rate of 2L/minute, yields charcoal with an enhanced calorific value of 6735 Kcal/kg. The primary aim of this research is twofold: first, to ascertain the optimal blend ratio of biomass and coal for co-firing, and second, to delineate the characteristics of the resultant co-firing mixture. The investigation reveals that the optimal blend ratio for co-firing stands at 10%, resulting in a calorific value of 5652 Kcal/kg. Furthermore, this ratio engenders a noteworthy reduction in sulphur content, decreasing from 0.805% to 0.453%, thereby satisfying the operational sulphur limit of <1% for power generation. Similarly, the optimal co-firing ratio for pyrolyzed coconut stem biomass is also found to be 10%, as its calorific value reaches 5852 Kcal/kg, aligning with the operational specifications stipulated for the boiler.